Plastisch- chirurgische Verfahren modifiziert nach Lexer zur Versorgung des Diabetischen Fußsyndroms in der Technischen Orthopädie – ein Standard im Hospital Geseke - Schraeder, Dirk Theodor; Geisen, Bärbel; Baumann, Dirk; Afaneh, Mamoun; Schafran, Tommy (Orthopädie Technik)

Joining of high-strength steel grades in lightweight structures using single-stage resistance element welding on conventional resistance spot welding machines - Günter, Heinrich; Meschut, Gerson (73rd IIW Annual Assembly and International Conference)

Value-centered design of a digital service robotics platform - Menzefricke, Jörn Steffen; Frank, Maximilian; Drewel, Marvin; Dumitrescu, Roman (Procedia CIRP)

Towards Meta-Algorithm Selection - Tornede, Alexander; Wever, Marcel Dominik; Hüllermeier, Eyke (Workshop MetaLearn 2020 @ NeurIPS 2020)

Identification of socio-technical changes caused by Industry 4.0 - Schnasse, Felix; Menzefricke, Jörn Steffen; Gabriel, Stefan; Hobscheidt, Daniela; Parlings, Matthias; Kühn, Arno; Dumitrescu, Roman (Proceedings of the Hamburg International Conference of Logistics (HICL))

Concept Development for a Functional Integrated Lightweight Battery Housing with Special Consideration of the Joining Technology - Krüger, Christopher; Schmolke, Tobias; Merdivan, David; Spohr, Sebastian; Urban, Peter; Meschut, Gerson

FOREL-Wegweiser: Handlungsempfehlungen für den ressourceneffizienten Leichtbau - Göddecke, Johannes; Meschut, Gerson; Gude, Maik; Lieberwirth, Holger; Tekkaya, Erman; Zaeh, Michael; Stegelmann, Michael; Müller, Michael; Böhme, Kurt; Krampitz, Thomas; Zöllner, Mareen; Hahn, Marlon; et al.

Experimentelle und numerische Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson; Teutenberg, Dominik; Ummenhofer, Thomas; Albiez, Matthias; Damm, Jannis; Matzenmiller, Anton; Kötz, Fabian (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Entwicklung und Qualifizierung einer rechnergestützten Auswertemethode zur Differenzierung der Versagensanteile klebtechnisch gefügter Proben - Ditz, Michael; Meschut, Gerson; Schwarze, Thomas; Smart, Dominic

The Interdisciplinary Development of an Educational Game for Primary School Children--Lessons Learned - Winkelnkemper, Felix; Schulte, Carsten; Eilerts, Katja; Bechinie, Dominik; Huhmann, Tobias (EdMedia+ Innovate Learning)

Specification of Software Requirements for Condition Monitoring of Automation Systems - Pasic, Faruk; Wohlers, Benedict (2020 IEEE Tenth International Model-Driven Requirements Engineering (MoDRE))

Aligning Strategy and Structure for Smart Service Businesses in Manufacturing - Koldewey, Christian; Gausemeier, Jürgen; Chohan, Nadia; Frank, Maximilian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the IEEE International Conference on Technology Management, Operations and Decisions ”Disruptive Technologies and Social Impacts”)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Reinhold, Jannik; Dumitrescu, Roman (ZWF Zeitschrift für wirtschaftliche Fabrikplanung)
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Planning a Smart Service Business Integrating External Partners - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Managing Digital Open Innovation)
Today’s manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding business models and value networks fundamentally differ from traditional ones. Developing smart services requires an advanced management of business models and new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to extend their business model portfolios and adapt their value networks. However, the highly complex transformation of value creation especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this chapter, we introduce a basic framework for designing smart services and present a methodology for the planning of a smart service business integrating external partners. The methodology is structured into five phases: Examination of smart service portfolio, analysis of business models and environment, business model portfolio planning, competence identification and analysis, and value creation planning. The methodology is explained by an example on cable marker printers.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Light diffraction in slab waveguide lenses simulated with the stepwise angular spectrum method - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
A stepwise angular spectrum method (SASM) for curved interfaces is presented to calculate the wave propagation in planar lens-like integrated optical structures based on photonic slab waveguides. The method is derived and illustrated for an effective 2D setup first and then for 3D slab waveguide lenses. We employ slab waveguides of different thicknesses connected by curved surfaces to realize a lens-like structure. To simulate the wave propagation in 3D including reflection and scattering losses, the stepwise angular spectrum method is combined with full vectorial finite element computations for subproblems with lower complexity. Our SASM results show excellent agreement with rigorous numerical simulations of the full structures with a substantially lower computational effort and can be utilized for the simulation-based design and optimization of complex and large scale setups.
Keywords: tet_topic_waveguides

Lebensdauerberechnung hybrider Verbindungen - Çavdar, Serkan; Teutenberg, Dominik; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B.; Tittmann, K.; Koch, I.; Jäger, H.; Wacker, J.-D.; Rybar, G.; et al. (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Berechnen der Lebensdauer hybrider Verbindungen - Çavdar, Serkan; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B.; Tittmann, K.; Koch, I.; Jäger, H.; Wacker, J.-D.; Rybar, G.; Melz, T. (DVS Congress 2020)

Fatigue life prediction of adhesively bonded FRP-aluminium-joints with hyperelastic behavior under cyclic multiaxial stress state - Çavdar, Serkan; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B. (Joining in Car Body Engineering 2020)

Prozesskettenbegleitende Vorgehensweise beim Mechanischen Fügen - Heyser, Per; Scharr, Christian; Nehls, Thomas; Wiesenmayer, Sebastian; Flügge, Wilko; Meschut, Gerson (4. Workshop Digitalisierung)

Hamstrings substitution via anteromedial portal with optional anterolateral ligament reconstruction is the preferred surgical technique for anterior cruciate ligament reconstruction: a survey among ESSKA members. - Vascellari, A; Grassi, A; Canata, GL; Zaffagnini, S; Gokeler, A; Jones, H (Knee Surg Sports Traumatol Arthrosc)